Bridging waitlist delays with Interim Buprenorphine Treatment: Initial feasibility - Sigmon, Stacey C. (Addict Behav, 2015)
Despite the effectiveness of agonist maintenance for opioid dependence, individuals can remain on waitlists for months, during which they are at significant risk for morbidity and mortality. Interim dosing, consisting of daily medication without counseling, can reduce these risks. In this pilot study, we examined the initial feasibility of a novel technology-assisted interim buprenorphine treatment for waitlisted opioid-dependent adults. Following buprenorphine induction during Week 1, participants (n=10) visited the clinic at Weeks 2, 4, 6, 8, 10 and 12 to ingest their medication under staff observation, provide a urine specimen and receive their remaining doses via a computerized Med-O-Wheel Secure device. They also received daily monitoring via an Interactive Voice Response (IVR) platform, as well as random call-backs for urinalysis and medication adherence checks. The primary outcome was percent of participants negative for illicit opioids at each 2-week visit, with secondary outcomes of past-month drug use, adherence and acceptability. Participants achieved high levels of illicit opioid abstinence, with 90% abstinent at the Week 2 and 4 visits and 60% at Week 12. Significant reductions were observed in self-reported past-month illicit opioid use (p<.001), opioid withdrawal (p<.001), opioid craving (p<.001) and ASI Drug composite score (p=.008). Finally, adherence with buprenorphine administration (99%), daily IVR calls (97%) and random call-backs (82%) was high. Interim buprenorphine treatment shows promise for reducing patient and societal risks during delays to conventional treatment. A larger-scale, randomized clinical trial is underway to more rigorously examine the efficacy of this treatment approach.